Simulation of electroplating process and influence mechanism for repairing inner and outer surfaces of a gold cup based on COMSOL multiphysics - Lifeng Ding; Chukun Qiao; Linhua Zhang; Qiang Li; Peiyu Gao; Jinhao Niu; Jiahao Zhang; Hongmei Dong (Results in Engineering)
Conventional restoration of metallic cultural relics often faces challenges due to procedural complexity and high costs. This study presents a COMSOL Multiphysics–based simulation approach to optimize the electroplating restoration of gold artifacts, establishing a digital conservation framework. A three-dimensional model simulated copper (Cu)–tin (Sn) alloy electrodeposition on a gold cup, incorporating a tertiary current distribution to couple the dynamics of the electric and chemical fields. Key findings reveal that edge effects cause the rim and handle tip to exhibit substantially higher current density than that by planar regions, thereby leading to nonuniform coating thickness. A homogeneous coating with 81.25 % Cu–Sn molar ratio is achieved through parameter optimization. Transient analysis demonstrates the critical influence of concentration polarization on the ion transport, providing both the theoretical understanding of and practical restoration strategies for metal artifacts.